Bronchial Stump Recurrence after Complete Resection of Lung Cancer: Effect of the Distance between the Tumor and Bronchial Resection Margin - Gunluoglu, Mehmet Zeki; Kocaturk, Celalettin Ibrahim; Demir, Adalet; Urer, Halide Nur; Dincer, Seyyit Ibrahim; Bedirhan, Mehmet Ali (The Thoracic and Cardiovascular Surgeon, 2018)
Purpose The purpose of this study was to evaluate the following parameters after complete resection in established lung cancer patients: the frequency of bronchial stump recurrence (BSR), the effect of the distance between the tumor and bronchial resection margin (DBTM) on BSR, the survival of patients with BSR, and the effect of the DBTM on survival.Patients and Methods We retrospectively evaluated 553 consecutive lung cancer patients who underwent complete lung resection. The patients were classified as DBTM: ≤ 10 mm (group 1), 11 to 20 mm (group 2), and > 20 mm (group 3).Results We found BSR in eight (1.5%) patients. Six patients were in group 1, and two were in group 2. The difference was found to be statistically significant (p = 0004; groups 1 vs. 3). In multivariable analysis, we observed a trend toward significance for the effect of a DBTM on BSR development (p = 0.1). The DBTM did not significantly affect survival (p = 0.61). The survival of patients who developed BSR was significantly poor compared with those who did not develop BSR (p = 0.001).Conclusion BSR can develop even after complete resection of lung cancer. The DBTM is associated with BSR risk, and the survival of patients who develop BSR is poor.
Keywords: lung cancer; surgery; local recurrence; bronchial stump